(untitled) (Global Journal of Science Frontier Research, 2018)
Aim of this study is to provide properties of a polynomial function on Fourier cosine and Fourier sine transform. Authors presented general properties of a polynomial function on Fourier cosine and Fourier sine transform by applying known results.